Circulating Cell-Free Tumor DNA in Advanced Pancreatic Adenocarcinoma Identifies Patients With Worse Overall Survival - Botrus, Gehan; Uson Junior, Pedro Luiz Serrano; Raman, Puneet; Kaufman, Adrienne E.; Kosiorek, Heidi; Yin, Jun; Fu, Yu; Majeed, Umair; Sonbol, Mohamad Bassam; Ahn, Daniel H.; Chang, Isabela W.; Drusbosky, Leylah M.; et al. (Frontiers in Oncology, 2022)
Background: Circulating cell-free tumor DNA (ctDNA) genomic profiling is an emerging tool for pancreatic cancer (PC). The impact of detected genomic alterations and variant allele fraction (VAF) in tumor response to systemic treatments and outcomes is under investigation. Methods: Patients with advanced PC who had ctDNA collected at time of initial diagnosis were retrospectively evaluated. We considered the somatic alteration with highest VAF as the dominant clone allele frequency (DCAF). CtDNA results were related to clinical demographics, progression-free survival (PFS) and overall survival (OS). Results: A total of 104 patients were evaluated. Somatic alterations were detected in 84.6 % of the patients. Patients with ≥ 2 detectable genomic alterations had worse median PFS (p < 0.001) and worse median OS (p = 0.001). CtKRAS was associated with disease progression to systemic treatments (80.4% vs 19.6%, p = 0.006), worse median PFS (p < 0.001) and worse median OS (p = 0.002). CtTP53 was associated with worse median PFS (p = 0.02) and worse median OS (p = 0.001). The median DCAF was 0.45% (0-55%). DCAF >0.45% was associated with worse median PFS (p<0.0001) and median OS (p=0.0003). Patients that achieved clearance of ctKRAS had better PFS (p=0.047), while patients that achieved clearance of ctTP53 had better PFS (p=0.0056) and OS (p=0.037). Conclusions: Initial detection of ctDNA in advanced PC can identify somatic alterations that may help predict outcomes. ctDNA dynamics is strongly related to outcomes and should be evaluated in prospective studies for confirmation of these prognostic findings.